Performance of the osmotic membrane bioreactor : investigation of extracellular polymeric substances (EPS) production under the influence of salinity and soluble microbial products - Ke, Derick Jianghao. (2011)
The forward osmotic membrane bioreactor is a viable water reclamation process combining the use of forward osmosis and the biological activated sludge. The FOMBRs possess high retention capability of organic matter and other contaminations. This results in an elevated salinity condition which may adversely affect the biological processes and performance of the FOMBR. This study aims to investigate the production of extracellular polymeric substances (EPS) under the influence of salinity and soluble microbial products (SMP). Comparisons will be made between a fed-batch “non- saline” source bioreactor and the lab scale FOMBR system. Evaluation of proteins and polysaccharides content will be used to determine the EPS production under fresh water, salinity and SMP conditions. Results showed that under the influences of 30mS/cm saline condition and SMP, the development of EPS are identical for the FOMBR system and source reactor and there were no significant differences in the EPS production. However, it is to be pointed out that soluble EPS production under the influence of SMP showed apparent different trends. This study provided evidence that there was no major differences in the EPS production under the given acclimation conditions. The elevated saline condition and retention of SMP in the FOMBR system did not have an adverse effect on EPS production.